Assessment Of Afasia in Stroke Patients: Case Study - Febryanto, Dwi; Retnaningsih; Handayani, Fitria (Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Introduction: Aphasia is understood as difficulty in understanding or producing language caused by disorders involving the brain hemispheres. Early assessment of aphasia is very important to prevent the emergence of telegraphic speech styles, improve welfare, independence, social participation, quality of life, reduce length of stay and care costs, but there is little literature on this subject, especially in stroke patients. Purpose: This study is to provide an overview of the assessment of aphasia in stroke patients. Methods: The design of a case study involving 6 participants and data collection was carried out by conducting an assessment using the Language Aphasia Screening Test (LAST) instrument which was monitored for 3 days, including monitoring errors for naming images, monitoring mismatches repeating words and sentences, monitoring spontaneous pronunciation, monitoring image comprehension, monitoring comprehension of verbal instructions.Results: A total of 6 ischemic stroke patients were found wrong in repeating words and sentences. Conclusion: In aphasic stroke patients all language modalities are impaired, ranging from spontaneous speech, repetition, naming, language comprehension, reading and writing